Aprendizagem musical: uma analise com vistas a identificação de Princípios para aprendizagem de instrumentos de sopro/madeira - Parente, Filipe Ximenes (2018)
This research focuses on a reflection about the learning process of the students involved in the disciplines of Woods I and II, with a view to identifying principles for wind instrument / wood learning. The research uses as central theoretical reference the studies of Paulo Freire (1996) on learning; the works of Pierre Bourdieu (2002) that conceptualize habitus and trajectory; the researches of Barbosa (1996); Yin (2007); Birth (2007); and Almeida (2014) to substantiate the work with musical groups. The methodology is qualitative (SILVA & SILVEIRA, 2007), focusing on a case study (GIL, 2009), which was preceded by an exploratory research (BASTOS, 2009). The plot is structured in an introduction, which presents the object of study, the contextualization of the research, the justification, the hypothesis and the objectives; followed by four chapters, namely: Chapter 1: theoretical assumptions of the musical field, in which we present the slopes for learning musical groups and situate the locus of the research; chapter 2: theoretical assumptions of the educational field, where we discuss learning, formation, experience, trajectory and curriculum; chapter 3: methodology, on which we base the methodological steps of the work; Chapter 4: Constructing a pedagogical approach to working with woodwind / wood instruments in the context of musical groups, in which we present some reflections on the presented study.